'Health and happiness is more important than weight': a qualitative investigation of the views of parents receiving written feedback on their child's weight as part of the National Child Measurement Programme. Issue 1 (12th February 2014) - Syrad, H.; Falconer, C.; Cooke, L.; Saxena, S.; Kessel, A. S.; Viner, R.; Kinra, S.; Wardle, J.; Croker, H.
Abstract Background The present study aimed to explore parental perceptions of overweight children and associated health risks after receiving National Child Measurement Programme (NCMP) weight feedback. Methods Fifty‐two parents of overweight and obese children aged 4–5 years and 10–11 years enrolled in the NCMP programme in England in 2010–2011 participated in qualitative, semi‐structured interviews about their perceptions of their child's weight and health risk after receiving weight feedback. Interviews were audio tape recorded and were conducted either by telephone (n = 9) or in the respondents' homes (n = 41). Interviews were transcribed verbatim and analysed using interpretative thematic analysis. Results Parents who received NCMP written feedback informing them that their child was overweight disregarded the results because they viewed 'health and happiness as being more important than weight'. The feedback was viewed as less credible because it did not consider the individual child's lifestyle. 'Broad definitions of healthy' were described that did not include weight, such as reference to the child having good emotional and physical health and a healthy diet. Parents attributed weight to 'inherited/acquired factors' such as genetics or puppy fat, or did not regard their child's 'appearance' as reflecting being overweight. 'Cultural influence' also meant that being overweight was not viewed negatively by some non‐white parents. Conclusions After receiving written weight feedback, parents use methods other than actual weight when evaluating their child's weight status and health risks. Parents' conceptions of health and weight should be considered when communicating with parents, with the aim of bridging the gap between parental recognition of being overweight and subsequent behaviour change.